2019
DOI: 10.3390/app9173509
|View full text |Cite
|
Sign up to set email alerts
|

A Biased-Randomized Iterated Local Search Algorithm for Rich Portfolio Optimization

Abstract: This research develops an original algorithm for rich portfolio optimization (ARPO), considering more realistic constraints than those usually analyzed in the literature. Using a matheuristic framework that combines an iterated local search metaheuristic with quadratic programming, ARPO efficiently deals with complex variants of the mean-variance portfolio optimization problem, including the well-known cardinality and quantity constraints. ARPO proceeds in two steps. First, a feasible initial solution is const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Video content attracts and engages users more, since it is deemed to be highly shareable and having a higher clickthrough rate compared to traditional text results [50]. In addition, the optimization of images helps search engines to determine easily what the image is about, and it is considered very important, especially for image-based search engines, such as Google Images [19]. Finally, links that lead to other relevant web pages (preferably high-ranking sites) can contribute positively to SEO, especially if a site is new [6,74].…”
Section: Seo and News Content Creation (Rq4)mentioning
confidence: 99%
See 1 more Smart Citation
“…Video content attracts and engages users more, since it is deemed to be highly shareable and having a higher clickthrough rate compared to traditional text results [50]. In addition, the optimization of images helps search engines to determine easily what the image is about, and it is considered very important, especially for image-based search engines, such as Google Images [19]. Finally, links that lead to other relevant web pages (preferably high-ranking sites) can contribute positively to SEO, especially if a site is new [6,74].…”
Section: Seo and News Content Creation (Rq4)mentioning
confidence: 99%
“…News websites, online radio and web TV, are the main areas of action. It is generally observed that the arrival of digital technologies has made journalistic work both easier, enabling better monitoring of economic and political organizations, and more difficult, overwhelming journalists with more information than they can handle [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the spirit of [44], we benchmark the strategies based on one single machine learning algorithm each against four strategies. The strategy ALL trades, if the average of the predicted goal differences yields less than −2 or more than +2.…”
mentioning
confidence: 99%
“…If the bus between nodes 5 and 6 breaks down, we set H (5,6) and H(6, 5) as zero. Then, the constraint is added.…”
Section: Example and Experimental Resultsmentioning
confidence: 99%
“…Zero-one quadratic programming, which can be divided into constrained (01CQP) and unconstrained (01UQP), is a combinatorial optimization and has practical significance. For example, it can be applied in circuit design [3], pattern recognition [4], capital budgeting [5], portfolio optimization [6], etc. Except for these well known applications, 01QP also has potential applications in the nonlinear control related fields [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%